Clinical and immunological features of antiphospholipid syndrome in the elderly: a retrospective national multicentre study. (3rd January 2019) - Grimaud, Felix; Yelnik, Cecile; Pineton de Chambrun, Marc; Amoura, Zahir; Arnaud, Laurent; Costedoat Chalumeau, Nathalie; Hachulla, Eric; Lambert, Marc; Roriz, Mélanie; Sibilia, Jean; Papo, Thomas; Sacre, Karim
Abstract: Objective: APS mainly affects women who are of child-bearing age. We aimed to describe the clinical and immunological features of APS patients diagnosed after the age of 60. Methods: The Elderly-Phospholipid study is a national, multicentre, retrospective study involving all APS (2006 Miyakis criteria) patients followed in five French tertiary university centres including four national referral lupus and APS centres. Clinical and serological data of patients in whom APS onset occurred after the age of 60 were analysed and compared with patients included in the Euro-Phospholipid cohort. Results: Forty-four patients (30 women (68.2%); 68.7 (7) years at diagnosis; 72.7% of primary APS) were included in the Elderly-Phospholipid study. Stroke was the most common manifestation at diagnosis (38.6%) and during follow-up (11.4%). LA, aCL and anti-β2 -glycoprotein I antibodies were detected in 70.4%, 72.7% and 65.9% of patients, respectively; 43.2% of patients were triple-positive for aPL antibodies. All patients were treated with antithrombotic treatment including antiplatelet agents (31.8%) and/or oral anticoagulants (77.3%). Over a 5.3 (3.8) years follow-up, nine (20.5%) patients displayed a new arterial ( n = 8) or venous ( n = 1) thrombotic event. Only three (6.8%) patients developed major bleeding . As compared with Euro-Phospholipid APS patients (mean age of 34 (13) years at disease onset), patients in the Elderly-Phospholipid study were more frequently male ( P < 0.05) and had a higher frequency of primary APS (<0.05), stroke (<0.0001) and LA ( P < 0.05). Conclusion: APS patients with elderly onset share a distinct disease profile, with a higher frequency of LA, triple aPL positivity and arterial thrombosis.